1985
DOI: 10.1111/j.1399-6576.1985.tb02190.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cardiopulmonary Bypass and Prostacyclin on Plasma Catecholamines, Angiotensin II and Arginine‐Vasopressin

Abstract: Infusion of prostacyclin during cardiopulmonary bypass (CPB) reduces platelet activation, diminishes postoperative blood loss and decreases arterial blood pressure. In spite of continuous prostacyclin infusion, there is a delayed gradual rise in arterial pressure and resistance from low initial levels. We measured epinephrine (E), norepinephrine (NE), serotonin (5-HT), angiotensin II (ATII) and arginine-vasopressin (AVP) in plasma and carried out hemodynamic studies in 19 patients operated for coronary vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…When PLA2 acts upon lipids containing arachidonic acid in the sn-2 position the resulting free arachidonic acid can serve as a substrate for cyclooxygenases and lipoxygenases. Platelet damage or excess secretion of humoral factors such as catecholamines or angiotensin II during cardiac surgery (14)(15)(16) has been implicated in the elevation of cellular PLA2 activity. Complement activation during CPB (17) causes chemotaxis and leukosequestration, together with the production of oxygen free-radicals by neutrophils, which is thought to affect PLA2 activity (18).…”
mentioning
confidence: 99%
“…When PLA2 acts upon lipids containing arachidonic acid in the sn-2 position the resulting free arachidonic acid can serve as a substrate for cyclooxygenases and lipoxygenases. Platelet damage or excess secretion of humoral factors such as catecholamines or angiotensin II during cardiac surgery (14)(15)(16) has been implicated in the elevation of cellular PLA2 activity. Complement activation during CPB (17) causes chemotaxis and leukosequestration, together with the production of oxygen free-radicals by neutrophils, which is thought to affect PLA2 activity (18).…”
mentioning
confidence: 99%
“…On the other hand, an excitation of the efferent cardiac sympathetic nerve fibers, which occurs after CAL (20) and is followed by a release of catecholamines, may be important for the rise in cardiac cyclic AMP. Whereas PGI2 or iloprost seem not to influence the latter catecbolamine release (34), a moderate effect of prostacyclin, lowering the blood noradrenaline level, has been demonstrated recently (10). Neither PGI2 nor iloprost administration caused a normalization in the cyclic AMP level to the preligation value, which has been found in the range of 0.5 to 0.7 pmol/mg wet weight in tissue freeze-clamped immediately after thoracotomy (3,7,17).…”
Section: Discussionmentioning
confidence: 96%
“…Whether endogenous serum vasopressin levels are adequate to sustain the systemic blood pressure and the response to the stressful postsurgical course is not known with certainty, decreased vasopressin serum levels have been observed in patients with hypotensive septic shock 15 . Studies of vasopressin during cardiac operations have shown increased serum levels during cardiopulmonary bypass, and a marked decrease of these levels in the early and late postoperative period 19,20 . These reduced postoperative levels may be insufficient to achieve an adequate stress response.…”
Section: Discussionmentioning
confidence: 99%